Composite material photocatalyst as well as preparation method and application thereof
Through the covalent bonding of indium-based ternary metal sulfide and β-ketoamine COFs, composite photocatalysts were prepared, which solved the problems of low efficiency and insufficient stability of existing photocatalysts, and achieved efficient photocatalytic H2O2 and good recycling and utilization.
Patent Information
- Application Number
- CN202411849744.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
AI Technical Summary
The existing photocatalysts have low efficiency in photocatalyzed H2O2 reactions, high carrier recombination efficiency, and insufficient stability of composite materials, which is not conducive to recycling.
The photocatalyst of composite material is formed by indium-based ternary metal sulfide and β-ketoamine covalent organic frame (COFs), and is prepared by ultrasonic, stirring and hydrothermal methods. The covalent bonding between metal and β-ketoamine COFs is used to improve carrier transport and separation capabilities.
The yield of photocatalytic H2O2 and the stability of composite materials are significantly improved, the recycling rate of photocatalytics are enhanced, and the photocatalytic performance is shown.
Smart Images

Figure CN119793485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to a composite material photocatalyst and a preparation method and application thereof. Background Art
[0002] Energy crisis and environmental pollution are two major global problems recognized today. For this reason, the production and utilization of clean energy and renewable energy have received more and more attention. Hydrogen peroxide (H2O2) is a recognized oxidant. Because of its active chemical properties and the fact that its decomposition products are only H2O and O2, it is widely used in metal etching, green chemical production, sewage treatment and other aspects. About 95% of the world's H2O2 is prepared by the traditional anthraquinone oxidation method, but this method has fatal disadvantages such as the need for large-scale infrastructure, energy intensiveness, complex preparation process, and many by-products. Among the many H2O2 synthesis strategies, photochemical synthesis is a recognized safe, green, and sustainable strategy for generating H2O2 by converting solar energy into chemical energy.
[0003] Among many photocatalysts, metal sulfides present a negative conduction band position due to their unique S 3p orbital advantage. At the same time, the narrower energy band and wider light response range make them exhibit superior carrier transport behavior. Compared with single metal sulfides, they have richer active sites due to the increase in metal species and show more satisfactory stability. Therefore, indium-based ternary metal sulfides have been widely used in photocatalysis in recent years. In particular, the unique and adjustable bimetallic sites facilitate the controllable adsorption of key intermediates. However, due to the low photocatalytic efficiency caused by slow electron transfer behavior and high carrier recombination efficiency, there is still a long way to go to achieve the goal of industrial application. In order to solve these problems, designed composite materials are widely used to optimize the interface structure and behavior of catalysts, thereby effectively improving the conversion efficiency and selectivity.
[0004] Chinese patent CN 109003827 A reported that the inventor used a simple high-pressure magnetic stirring one-pot method to prepare a sponge-like graphene / nickel cobalt sulfide composite material. The resulting composite material has a larger specific surface area, which allows it to fully contact the electrolyte and significantly improves its electrochemical performance. In Chinese patent CN 111180694 A, the inventor mixed and stirred a metal salt with a MXene material to obtain a MXene / metal salt mixture, and then mixed it with a sulfur source under a protective atmosphere and heat-treated it to obtain a MXene / metal sulfide composite material with high energy density and excellent rate performance. However, under traditional composite methods, the composite between sulfide and other materials may lead to weak interactions between them, resulting in insufficient stability of the composite material, which is not conducive to the recycling of photocatalysts.
[0005] Compared with other photocatalyst materials, covalent organic frameworks (COFs) represent an emerging type of crystalline porous polymers with unique ordered channel structures, tunable topological structures and units, and high chemical and thermal stability. From a structural point of view, the optical and electronic properties of photoactive COFs can be easily adjusted by adjusting the building blocks and regulating the morphology, which also opens up new opportunities for the design and development of new attractive photocatalysts. Among them, β-ketoamine COFs are prepared by irreversible enol to keto tautomerism. This type of COFs has high crystallinity and exhibits high stability under severe conditions such as boiling water, strong acid, and strong base. Moreover, the unique keto sites on β-ketoamine COFs can form covalent bonds with indium-based ternary metal sulfides. The covalent bonding between indium-based ternary metal sulfides and COFs makes the composite structure more stable and enhances the transport and separation capabilities of photogenerated carriers, which is beneficial to photocatalytic reactions. Summary of the invention
[0006] The purpose of the present invention is to provide a composite material photocatalyst in order to improve the deficiencies of the prior art. Another purpose of the present invention is to provide a method for preparing the composite material photocatalyst. Another purpose of the present invention is to provide an application of the composite material photocatalyst, which is a metal semiconductor with superior performance, namely, indium-based ternary metal sulfide and β-ketoamine COFs which also have superior performance in photocatalysis. The indium-based ternary metal sulfide and β-ketoamine covalent organic framework composite material catalyst obtained by simple methods such as ultrasound, stirring and hydrothermal is used to produce H2O2 under photocatalysis, has efficient H2O2 production capacity, and has the advantages of being green, environmentally friendly and economically recyclable.
[0007] For most traditional composite catalyst materials, the composite mode between photocatalysts leads to weak interaction, resulting in low photocatalytic performance and insufficient stability of the material. However, the present invention utilizes the unique covalent bonding between metal on metal sulfide and β-ketoamine COFs to achieve efficient separation and transportation of photogenerated carriers while enhancing the stability of the composite material, which is ultimately reflected in the excellent photocatalytic H2O2 yield and reusability of the composite material.
[0008] The technical solution of the present invention is: a composite material photocatalyst, characterized in that: the composite material photocatalyst comprises an indium-based ternary metal sulfide (M n In x S y ) and β-ketoamine covalent organic framework (R-TH-COF), the two form a composite material under covalent bonding; the chemical formula of the composite material is: R-TH-COF@M n In x S y ;
[0009] Wherein: M is Mg, Zn, Ag, Ca or Cd; In is metal indium; S is sulfur;
[0010] n:x:y=1:(1~2):(2~4); R-TH-COF and M n In x S y The mass ratio is 1:(1~6);
[0011] R is
[0012] The chemical structure of β-ketoamine covalent organic framework R-TH-COF is:
[0013]
[0014] The present invention also provides a method for preparing the composite material photocatalyst, and the specific steps are as follows:
[0015] Step 1: Preparation of β-ketoamine covalent organic framework by solvothermal method: trialdehyde phloroglucinol TH and R-based monomer are mixed and placed in a glass container, a mixed organic solvent is added, and the mixture is homogenized by ultrasonication and then frozen in liquid nitrogen, vacuumized to remove air and then thawed, and the freezing-vacuuming-thawing operation is repeated 2 to 4 times, and the glass container is sealed, and after the glass container is cooled, it is placed in an oven and reacted at 90 to 150° C. for 48 to 96 hours; after the reaction is completed, the solid powder is filtered out and washed, and finally the sample is dried and collected in a vacuum blower to obtain a β-ketoamine covalent organic framework;
[0016] Step 2: preparing a metal and β-ketoamine covalent organic framework precursor: adding the β-ketoamine covalent organic framework obtained in step 1 to an alcohol solvent, uniformly dispersing it by ultrasonication, and then adding metal M chloride and indium chloride and stirring for 1 to 2 hours;
[0017] Step 3: Preparation of composite photocatalyst: Add sulfur source to the metal and β-ketoamine covalent organic framework precursor obtained in step 2, transfer all to a hydrothermal kettle and react at 150-220°C for 10-18h; after the reaction is complete, cool, clean and dry in an oven to obtain a composite material.
[0018] Preferably, in step 1, the molar ratio of trialdehyde phloroglucinol to R-group monomer is 2:(1-4); the mixed organic solvent is composed of pyrrolidine, n-butanol and o-dichlorobenzene in a volume ratio of 1:(25-2):(50-25), and the mixed organic solvent is added until the monomer is dissolved; after the reaction is completed, the solid powder is filtered out and washed with N,N-dimethylacetamide, acetone and dichloromethane for 2-4 times in sequence.
[0019] Preferably, the alcohol solvent in step 2 is any one or two of methanol, ethanol, ethylene glycol or glycerol; the volume ratio of the mass of indium chloride to the alcohol solvent is 1.5-4 g / L.
[0020] Preferably, the sulfur source in step 3 is any one of thioacetamide, sodium sulfide or thiourea; after the reaction is completed, the solid powder obtained is washed with water and ethanol respectively for 2 to 3 times.
[0021] The present invention also provides the use of the composite material photocatalyst in photocatalytic production of hydrogen peroxide, and other unknown related fields can also be applied. The indium-based ternary metal sulfide and β-ketoamine COFs composite material photocatalyst synthesized by the present invention can produce hydrogen peroxide under light conditions.
[0022] Compared with the closest prior art, the technical solution provided by the present invention has the following beneficial effects:
[0023] 1) The present invention adopts a method of first allowing β-ketoamine COFs to fully covalently bond with metals to form a precursor and then adding a sulfur source to form a composite material. This method is not only simple and easy to operate, and has mild conditions, but also allows the indium-based ternary metal sulfide and β-ketoamine COFs to form a covalent bond better, which is beneficial to the formation of interaction between the composite materials.
[0024] 2) A unique covalent bonding interaction is formed in the indium-based ternary metal sulfide and β-ketoamine COFs composite material synthesized by the present invention, which is beneficial to the separation and transportation of photogenerated carriers, greatly promotes the oxidation-reduction ability of the photocatalyst, and exhibits excellent photocatalytic H2O2 production performance.
[0025] 3) The indium-based ternary metal sulfide and β-ketoamine COFs composite material synthesized by the present invention greatly improves the stability of photocatalysis; it still maintains stable performance after multiple cycles of use, thereby improving the recycling rate of the photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of Bt-TH-COF in Example 1 of the present invention;
[0027] Figure 2 This is the SEM image of Bt-TH-COF@MgIn2S4 in Example 1 of the present invention;
[0028] Figure 3 In 3d XPS spectra of MgIn2S4 and Bt-TH-COF@MgIn2S4 in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] [Example 1]: Preparation of Bt-TH-COF@MgIn2S4 composite material
[0031] 16.80 mg (0.08 mmol) of trialdehyde phloroglucinol (TH) and 38.20 mg (0.12 mmol) of 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl) diphenylamine (Bt) were mixed and placed in a glass bottle, and a mixed solution of 20 μL of pyrrolidine, 0.95 mL of o-dichlorobenzene and 0.050 mL of n-butanol was added, and the mixture was homogenized by ultrasonication and frozen in liquid nitrogen, vacuumed to remove air and then thawed. After repeating the freezing-vacuuming-thawing operation three times, the glass bottle was sealed, and after the glass bottle was cooled, it was placed in an oven and reacted at 120°C for 72 hours. After the reaction was completed, the solid powder was filtered out and washed three times with N, N-dimethylacetamide, acetone and dichloromethane in sequence, and finally the sample was dried in a vacuum blower and collected to obtain Bt-TH-COF. Figure 1 The SEM images demonstrated the successful synthesis of Bt-TH-COF.
[0032] Take 20 mg of the synthesized Bt-TH-COF and place it in a container with 20 mL of ethylene glycol. After ultrasonication until Bt-TH-COF is evenly dispersed, add 11.40 mg (0.12 mmol) of MgCl2 and 70.38 mg (0.24 mmol) of InCl3·4H2O. After stirring at room temperature for 1 hour, add 73.63 mg (0.98 mmol) of thioacetamide. Transfer all the above mixtures to a hydrothermal autoclave and react at 180°C for 12 hours. After the reaction is complete, cool it, wash it with water and ethanol three times, and dry it in an oven overnight to obtain a Bt-TH-COF@MgIn2S4 composite material. The mass ratio of Bt-TH-COF to MgIn2S4 in the composite material is 1:3.25. Figure 2 The SEM images of Bt-TH-COF@MgIn2S4 demonstrate the successful composite Figure 3 In 3d XPS spectra of MgIn2S4 and Bt-TH-COF@MgIn2S4, proving the formation of covalent bonding in Bt-TH-COF@MgIn2S4.
[0033] [Example 2]: Preparation of DAPT-TH-COF@ZnIn2S4 composite material
[0034] 16.80 mg (0.08 mmol) of trialdehyde phloroglucinol (TH) and 41.65 mg (0.08 mmol) of 4,4'-diaminoterphenyl (DAPT) were mixed and placed in a glass bottle, and a mixed solution of 20 μL of pyrrolidine, 0.80 mL of o-dichlorobenzene and 0.20 mL of n-butanol was added. After ultrasonic homogenization, the mixture was frozen in liquid nitrogen, vacuumed to remove air and then thawed. After repeating the freezing-vacuuming-thawing operation twice, the glass bottle was sealed, and after the glass bottle was cooled, it was placed in an oven and reacted at 110°C for 96 hours. After the reaction was completed, the solid powder was filtered out and washed twice with N,N-dimethylacetamide, acetone and dichloromethane in sequence. Finally, the sample was dried in a vacuum blower and collected to obtain DAPT-TH-COF. DAPT-TH-COF was successfully synthesized.
[0035] 25 mg of the synthesized DAPT-TH-COF was placed in a container containing 30 mL of propylene glycol. After ultrasonication until DAPT-TH-COF was evenly dispersed, 12.06 mg (0.12 mmol) of ZnCl2 and 70.38 mg (0.24 mmol) of InCl3·4H2O were added. After stirring at room temperature for 2 hours, 76.50 mg (0.98 mmol) of sodium sulfide was added. The above mixture was transferred to a hydrothermal autoclave and reacted at 200 ° C for 14 hours. After the reaction was complete, it was cooled and washed twice with water and ethanol and dried in an oven overnight to obtain a DAPT-TH-COF@ZnIn2S4 composite material. A covalent bond was successfully formed between DAPT-TH-COF and ZnIn2S4. The mass ratio of DAPT-TH-COF to ZnIn2S4 in the composite material was 1:2.34.
[0036] [Example 3]: Preparation of DADP-TH-COF@CdIn2S4 composite material
[0037] 16.80 mg (0.08 mmol) of trialdehyde phloroglucinol (TH) and 14.74 mg (0.08 mmol) of 4,4'-diaminobiphenyl (DADP) were mixed and placed in a glass bottle, and a mixed solution of 20 μL of pyrrolidine, 0.60 mL of o-dichlorobenzene and 0.40 mL of n-butanol was added. After ultrasonic homogenization, the mixture was frozen in liquid nitrogen, vacuumed to remove air and then thawed. After repeating the freezing-vacuuming-thawing operation four times, the glass bottle was sealed, and after the glass bottle was cooled, it was placed in an oven and reacted at 150°C for 54 hours. After the reaction was completed, the solid powder was filtered out and washed four times with N, N-dimethylacetamide, acetone and dichloromethane in sequence, and finally the sample was dried in a vacuum blower and collected to obtain DADP-TH-COF.
[0038] 10 mg of the synthesized DADP-TH-COF was placed in a container with 40 mL of ethanol. After ultrasonication until DADP-TH-COF was evenly dispersed, 22.00 mg of CdCl2 (0.12 mmol) and 70.38 mg (0.24 mmol) of InCl3·4H2O were added. After stirring at room temperature for 1 hour, 57.94 mg (0.98 mmol) of thiourea was added. The above mixture was transferred to a polytetrafluoroethylene hydrothermal autoclave and reacted at 220 ° C for 16 hours. After the reaction was complete, it was cooled and washed with water and ethanol three times and dried in an oven overnight. The DADP-TH-COF@CdIn2S4 composite material was successfully synthesized. The mass ratio of DADP-TH-COF to CdIn2S4 in the composite material was 1:5.64.
[0039] [Example 4]: Preparation of DAB-TH-COF@AgInS2 composite material
[0040] 16.80 mg (0.08 mmol) of trialdehyde phloroglucinol (TH) and 4.33 mg (0.04 mmol) of p-phenylenediamine (DAB) were mixed and placed in a glass bottle, and a mixed solution of 20 μL of pyrrolidine, 0.50 mL of o-dichlorobenzene and 0.50 mL of n-butanol was added, and the mixture was frozen in liquid nitrogen after ultrasonic homogenization, and the air was removed by vacuum and then thawed. After repeating the freezing-vacuuming-thawing operation four times, the glass bottle was sealed, and after the glass bottle was cooled, it was placed in an oven and reacted at 90° C. for 96 hours. After the reaction was completed, the solid powder was filtered out and washed three times with N, N-dimethylacetamide, acetone and dichloromethane in sequence, and finally the sample was dried in a vacuum blower and collected to obtain DADP-TH-COF.
[0041] 30 mg of the synthesized DADP-TH-COF was placed in a container with 25 mL of ethanol. After ultrasonication until DADP-TH-COF was evenly dispersed, 17.20 mg of AgCl (0.12 mmol) and 35.19 mg (0.12 mmol) of InCl3·4H2O were added. After stirring at room temperature for 2 hours, 36.82 mg (0.49 mmol) of thioacetamide was added. The above mixture was transferred to a polytetrafluoroethylene hydrothermal reactor and reacted at 220°C for 16 hours. After the reaction was complete, it was cooled, washed with water and ethanol four times, and dried in an oven overnight to obtain a DADP-TH-COF@CdIn2S4 composite material. The mass ratio of DAB-TH-COF to AgInS2 in the composite material was 1:1.14.
[0042] [Application Example]: Take 30 mg of Bt-TH-COF@MgIn2S4, DAPT-TH-COF@ZnIn2S4, DADP-TH-COF@CdIn2S4 and DAB-TH-COF@AgInS2 respectively and disperse them in 30 mL of 10% IPA aqueous solution; then protect the system from light and allow oxygen to flow for 30 minutes, then irradiate with a xenon lamp (λ>420nm) and time it, take samples every 30 minutes, and finally test the absorbance of the catalyst under a UV spectrophotometer and calculate its concentration.
[0043] Table 1 Photocatalytic performance of hydrogen peroxide production by different catalysts
[0044] Photocatalyst <![CDATA[Performance (μmol g -1 h -1 )]]> <![CDATA[Bt-TH-COF@MgIn2S4]]> 1284.84 <![CDATA[DAPT-TH-COF@ZnIn2S4]]> 899.56 <![CDATA[DADP-TH-COF@CdIn2S4]]> 783.92 <![CDATA[DAB-TH-COF@AgInS2]]> 1089.32
[0045] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A composite material photocatalyst, characterized in that: The composite photocatalyst includes an indium-based ternary metal sulfide (M n In x S y ) and β-ketoamine covalent organic framework (R-TH-COF), the two form a composite material under covalent bonding; the chemical formula of the composite material is: R-TH-COF@M n In x S y ; Wherein: M is Mg, Zn, Ag, Ca or Cd; In is metal indium; S is sulfur; n:x:y=1:(1~2):(2~4); R-TH-COF and M n In x S y The mass ratio is 1:(1~6); R is The chemical structure of β-ketoamine covalent organic framework R-TH-COF is:
2. A method for preparing the composite material photocatalyst as claimed in claim 1, wherein the specific steps are as follows: Step 1: Preparation of β-ketoamine covalent organic framework by solvothermal method: trialdehyde phloroglucinol TH and R-based monomer are mixed and placed in a glass container, a mixed organic solvent is added, and the mixture is homogenized by ultrasonication and then frozen in liquid nitrogen, and the air is removed by vacuumization and then thawed. After repeating the freezing-vacuuming-thawing operation 2 to 4 times, the glass container is sealed, and after the glass container is cooled, it is placed in an oven and reacted at 90 to 150° C. for 48 to 96 hours. After the reaction is completed, the solid powder is filtered out and washed, and finally the sample is dried and collected to obtain a β-ketoamine covalent organic framework. Step 2: preparing a metal and β-ketoamine covalent organic framework precursor: adding the β-ketoamine covalent organic framework obtained in step 1 to an alcohol solvent, uniformly dispersing it by ultrasonication, and then adding metal M chloride and indium chloride and stirring for 1 to 2 hours; Step 3: Preparation of composite photocatalyst: Add sulfur source to the metal and β-ketoamine covalent organic framework precursor obtained in step 2, transfer all to a hydrothermal kettle and react at 150-220°C for 10-18h; after the reaction is complete, cool, clean and dry in an oven to obtain a composite material.
3. The method according to claim 2, characterized in that: In the step 1, the molar ratio of trialdehyde phloroglucinol to R-based monomer is 2:(1-4); the mixed organic solvent is composed of pyrrolidine, n-butanol and o-dichlorobenzene in a volume ratio of 1:(25-2):(50-25); after the reaction is completed, the solid powder is filtered out and washed with N,N-dimethylacetamide, acetone and dichloromethane for 2-4 times in sequence.
4. The method according to claim 2, characterized in that: In the step 2, the alcohol solvent is any one or two of methanol, ethanol, ethylene glycol or glycerol; the volume ratio of the mass of indium chloride to the alcohol solvent is 1.5-4 g / L.
5. The method according to claim 2, characterized in that: The sulfur source in step 3 is any one of thioacetamide, sodium sulfide or thiourea; after the reaction is completed, the solid powder obtained is washed with water and ethanol respectively for 2 to 3 times.
6. Use of the composite material photocatalyst as claimed in claim 1 in photocatalytic production of hydrogen peroxide.
Citation Information
Patent Citations
AgInS2 nanoflower having visible light photocatalytic oxidation and photocatalytic reduction capabilities, and preparation and applications thereof
CN106031875A
AgIn5S8 / UIO-66-NH2 composite material with high visible-light activity, and preparation method and application thereof
CN108993604A
Visible light composite photocatalyst capable of efficiently producing hydrogen peroxide
CN114870898A
Hybrid material based on photosensitive metal-organic coordination nanocage and covalent organic framework as well as preparation method and application of hybrid material
CN117019223A
Covalent organic framework photocatalytic material as well as preparation method and application thereof
CN117304430A